THE ROLE OF LIBRARY IN DEVELOPING LITERACY OF SD N 4 KUTOSARI STUDENT - Nurjihan Hasanah; Listiyani Listiyani; Solikhatun Diniah; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This title of research: “The role of library in developing literacy of SD N 4 Kutosari Student”. The focus of the study in this research is: (1) How the role of library in developing literacy of SD N 4 Kutosari Student ? (2) How the impact of library in in developing literacy of SD N 4 Kutosari Student ? Based on the formulation of the problem, this research has purposes: (1) Identify role of libraries in developing literacy of SD N 4 Kutosari Student. (2) Identify the impact of library in developing literacy of SD N 4 Kutosari Student. Techniques of data collection in this research are through literacy reading on cases, proceed with the questionnaire distribution, and lastly by drawing the conclusion.